2016
DOI: 10.1111/edt.12305
|View full text |Cite
|
Sign up to set email alerts
|

Drill‐related root injury caused by intraoperative intermaxillary fixation: an analysis of 1067 screw applications

Abstract: Intermaxillary fixation with predrilled transgingival screws is a safe way to manage mandibular fractures. The incidence of tooth root injury is not uncommon, but the adverse side effects are rare and the health of the affected teeth is mostly not compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…Among these, only a single tooth required intervention with root canal treatment. [12][13][14][15][16][17][18][19] In our study, buried screw heads were found among all the 21 patients of HAB. Over 137 out of 252 screw heads were covered with soft tissue at the end of the 4th week.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Among these, only a single tooth required intervention with root canal treatment. [12][13][14][15][16][17][18][19] In our study, buried screw heads were found among all the 21 patients of HAB. Over 137 out of 252 screw heads were covered with soft tissue at the end of the 4th week.…”
Section: Discussionsupporting
confidence: 48%
“…• No soft tissue covering the screw head: 0 • Soft tissue covering not more than half the screw head: 1 • Soft tissue covering more than half the screw head: 2 • Soft tissue completely covering the screw head: 3 This index was recorded for each screw in the upper and lower arch. The total score was divided by the number of screws (12) evaluated to obtain a screw head soft tissue coverage score.…”
Section: Methodsmentioning
confidence: 99%
“…Iatrogenic damage to roots of adjacent is the most common complication observed with transalveolar screws [6,[17][18][19]. Estimation of major and minor contacts was done on radiographic evaluation after the removal of screws based according to study by Fabbroni et al [17], contacts were judged to be major if more than 50% of the diameter of the screw hole impinged on the root of adjacent tooth and minor if less than 50% of diameter of screw hole was in contact with adjacent root (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It helps to immobilize fractures while promoting the healing process. In 460 bc , Hippocrates first introduced the concept of IMF by using gold wire to secure proper occlusion 1,2 . Intermaxillary fixation can be achieved by many different methods such as eyelets, arch bars, orthodontic brackets, cast metal splints, vacuum-formed splints, steel wires, and skeletal anchorage system 3–5 .…”
mentioning
confidence: 99%
“…In 460 BC, Hippocrates first introduced the concept of IMF by using gold wire to secure proper occlusion. 1,2 Intermaxillary fixation can be achieved by many different methods such as eyelets, arch bars, orthodontic brackets, cast metal splints, vacuum-formed splints, steel wires, and skeletal anchorage system. [3][4][5] Despite long operation time and higher risk for needle stick injury, the arch bar has become the standard of care due to its versatility, reliability, and cost-effectiveness.…”
mentioning
confidence: 99%